Petrology and structure of a portion of the pЄ Mullen Creek metaigneous mafic complex, Medicine Bow Mountains, Wyoming - Donnelly, Michael Edward, author; McCallum, M. E., advisor; Warren, C. G., committee member; Burns, L. K., committee member (Colorado State University. Libraries, 1979)
The Mullen Creek mafic complex, located in the central Medicine Bow Mountains of Wyoming, is a Precambrian sequence of layered metaigneous mafic rocks intruded by several small, irregular plutons of felsic composition. The sequence consists of a diversified assemblage of rock types that exhibit variable degrees of regional and kinetic metamorphism as well as hybridization resulting from subsequent intrusion of felsic bodies. The main mafic body is a layered metagabbroic mass that has undergone gravitational differentiation to form gabbro-anorthositic gabbro-anorthosite-pyroxenite differentiates. Convectional motion appears to have been operative during crystallization as evidenced by cross-bedding, scour channeling, igneous laminations, and localized rhythmic layering. Systematic changes in the bulk composition of the layered sequence are suggested by increasing phosphorous, sodium, titanium, vanadium, zirconium, iron to magnesium ratio, and decreasing nickel in similar units with increasing stratigraphic height. Reversals in compositional variations are indicated by mineralogic and geochemical changes. Diabase, late stage gabbro, two periods of basalt dikes, and a minimum of two felsic phases intrude the layered sequence. One felsic body, the Horse Creek granodiorite, may represent a late stage differentiate of the layered gabbroic sequence. Regional amphibolite grade metamorphism has masked most of the primary mineralogy of the mafic units, but numerous relict textures are present throughout most of the complex. A late stage of kinetic metamorphism at lower amphibolite -upper greenschist facies has imparted a cataclastic and accompanying retrograde metamorphic overprint locally. Emplacement of younger felsic rocks during the waning stages of the regional metamorphic event is responsible for hybridization of surrounding mafic units. The mafic complex has been subjected to at least two folding episodes and multiple episodes of faulting and shearing. The complex has been folded anticlinally about a slightly overturned axis plunging steeply to the northwest with indeterminate internal folding. Refolding is reflected by a shallow westerly trending synanticlinical fold. Local shearing produced a penetrative fabric that subparallels the Mullen Creek-Nash Fork shear zone. Many Precambrian faults apparently were reactivated during the Laramide orogeny.
Includes two maps (plate I, plate II).
Keywords: Geology -- Medicine Bow Mountains (Colo. and Wyo.)